1998
DOI: 10.1080/10715769800300411
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant status and dialysis: Plasma and saliva antioxidant activity in patients with fluctuating urate levels

Abstract: The present study is concerned with the influence of processes occurring during dialysis on the antioxidant capacity of plasma and saliva. The biological fluids were also tested for uric acid and total protein content. Before hemodialysis, plasma antioxidant status of hemodialyzed patients appears slightly higher than the corresponding status in normal subjects; after hemodialysis it is found unchanged. The result can be explained by a balance between a reduction in uric acid plasma content, due to the dialyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 22 publications
7
33
0
Order By: Relevance
“…To the best of our knowledge, our results regarding salivary TAS in hemodialyzed patients are novel, as are the results obtained for the salivary antioxidant enzymes peroxidase and SOD, and the results concerning UA in dialyzed DM patients. Nevertheless, the results demonstrated are partially supported by the study of Meucci et al [38] who showed a reduction in the salivary UA concentrations of CRF patients without DM following dialysis, while a reduction in serum TAS levels following dialysis was shown by Mayer et al [42]. The increase in salivary TAS values in the severe-CRF- with -DM patients (group 2) may be explained by the increase in the salivary antioxidant SOD enzyme, which may reflect a response aimed at compensating for the oxidative stress induced by dialysis.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…To the best of our knowledge, our results regarding salivary TAS in hemodialyzed patients are novel, as are the results obtained for the salivary antioxidant enzymes peroxidase and SOD, and the results concerning UA in dialyzed DM patients. Nevertheless, the results demonstrated are partially supported by the study of Meucci et al [38] who showed a reduction in the salivary UA concentrations of CRF patients without DM following dialysis, while a reduction in serum TAS levels following dialysis was shown by Mayer et al [42]. The increase in salivary TAS values in the severe-CRF- with -DM patients (group 2) may be explained by the increase in the salivary antioxidant SOD enzyme, which may reflect a response aimed at compensating for the oxidative stress induced by dialysis.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, it has previously been widely reported that blood levels of vitamins E and C, UA, glutathione, peroxidase and total antioxidant capacity of dialytic patients decrease, while the levels of AGEs increase [29,30,31,35,36,37]. Unfortunately, the oxidative stress-related alterations in the saliva of CRF patients have been only partially examined and published in only one paper [38], and results of saliva analysis in patients suffering from the concurrent effect of both CRF and DM or of both severe CRF and hemodialysis have never been published. These are surprising, considering the fact that the salivary antioxidant system is of fundamental regional importance, as it also represents the patient’s systemic oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…In oxidative stress, an imbalance between production of free radicals and antioxidant levels leads to an increase in ROS levels in the biological environment. Overproduction of ROS causes destruction of some bio-molecules, including DNA, amino acids, carbohydrates, lipids, and disturbance in structural organization and cell function (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is that an increase in activity of peroxidase is due to a rise in oxidative status of oral cavity in ulcerative cases. 21 Fluctuations in salivary peroxidase have been drawing increased attention during the last two decades 22,23 as it plays important role in the oral defense mechanism and attack of free radicals. It has been reported that peroxidase in saliva can significantly inhibit the initiation and progression of oral cancer.…”
Section: Discussionmentioning
confidence: 99%